(untitled) (Revista Brasileira Multidisciplinar, 2024)
The World Health Organization estimates that severe periodontal disease affects about 14% of the global adult population, representing more than one billion cases worldwide. Periodontal disease (PD) is triggered by the host’s immune response against pathogenic microorganisms in the dental biofilm and is characterized by the destruction of gingival tissue, alveolar bone and connective tissues that support the tooth. The biofilm, composed of bacteria, stimulates the process of local inflammation generated by the increase in cytokines, inflammatory cells such as macrophages, B and T cells. The balance between the virulence of the local biofilm and the host’s immune response influences the progression and severity of the disease periodontal. Several factors and systemic conditions can interfere and modulate the host response, and the relationship between periodontal disease and systemic disease is bidirectional, that is, periodontal disease can lead to adverse systemic outcomes, and certain systemic diseases predispose individuals to periodontal disease. There are several species of pathogens abundant in the oral cavity, mainly Gram-negative anaerobic bacteria, which produce endotoxins that directly contribute to systemic diseases. Recent studies have demonstrated possible mechanisms by which periodontitis may increase susceptibility to systemic diseases. This literature review sought to present the possible relationship between periodontal disease and rheumatoid arthritis, diabetes mellitus and cardiovascular diseases through a bibliographic survey carried out in the following databases: PubMed, PERIODICOS CAPES, MEDLINE, LILACS and the Virtual Health Library, in order to elucidate such mechanisms of action between PD and these systemic diseases. Given this research, it can be concluded that periodontal disease and systemic health have a bidirectional association.